Dialogues of Indigenous Afro-Latinxs (re)existence: Possible decolonialities (Alternautas, 2022)
This article is the result of the dialogue started in the symposium "Decolonizing the Global North: Afro-Latin America, the Caribbean and Abya Yala in Diaspora" during the International Congress of Americanists (56th ICA 2018). Written by eight hands in the format of a conversation, this text aims to expose the conditions of oppression experienced by indigenous and Afro-Latinx peoples from two positionalities. The first is the voice of researchers immersed in their given settings. This is followed by the comments of peer researchers addressing issues related to institutional racism, the exploitation and use of land, and the construction of identities and queer spaces from a decolonial perspective. This dialogue attempts to point toward possible horizons of liberation from exchanges that can build networks of solidarity.